Exercise at home program “DomiGym” contributes to the prevention of falls in vulnera-ble elderly people - Endes, Simon; Manike, Katja; Roth, Ralf; Stoffel Kerr, Sonja D.; Lehmann, Julia; Kraft, Eliane (Current Issues in Sport Science (CISS), 2023)
Background Eighty-eight thousand fall accidents occur each year in Switzerland among people aged 65 and over, which cause a lot of personal suffering and economic costs Beratungsstelle für Unfallverhütung BFU, 2019). The exercise at home program “DomiGym - Bewegungsangebot zu Hause” (in short: DomiGym) of Pro Senectute Switzerland aims to maintain mobility, counteract the risk of falls and promote social contacts as well as social participation and psychosocial health. Vulnerable, elderly people enjoy with DomiGym an adapted, regular training program focused on strength and balance, in their own homes or in their neighborhoods. Methodology The implementation and effects of the DomiGym offers in the cantons of Zug and Zurich were evaluated using various methodological approaches: tests of strength (Chair-Stand-Test; Mehmet et al., 2019), of balance (Modified Romberg; Agrawa et al., 2011) and of functional mobility (Timed-Up-and-Go-Test; Marks, 2016) as well as written surveys of participants (based on standardized scales used in the Swiss Health Survey). Results On average participants reduced fall risk and improved functional mobility and leg strength (p < 0.05). In a subsample of the canton of Zug, the Timed-Up-and-Go-Test (functional mobility and fall risk) improved by an average of 2.3 seconds (p < 0.005) and the balance test (Romberg) improved by 1.8 seconds (p = 0.005). Over the course of a training series the reduction in fall risk proved clinically relevant in both cantons. Scores on the Timed-Up-and-Go-Test fell on average below the threshold of 13.5 seconds discriminating between fallers and non-fallers. Chair-stand test: Participants improved on average from an initial very high fall risk to an increased fall risk (below 15 seconds). In fact the subsample of canton Zug improved by an average of 3.96 seconds (clinically relevant with regard to the reduction of falls) and the subsample of canton Zurich improved by an average of 2.17 seconds (approximately clinically relevant; threshold value 2.3 seconds; Meretta et al., 2006). DomiGym improved the general health (67%) of most participants and either maintained the original walking level (80%) or even improved it (15%). The majority of DomiGym participants do gymnastic exercises at least weekly outside of DomiGym training. DomiGym participants positively change their movement behavior in everyday life. Conclusions Pro Senectute’s DomiGym reaches older people who cannot or do not want to attend out-of-home physical activity programs. The implementation of DomiGym improves the physical functions of leg strength, functional mobility, and balance, as well as the risk of falls in vulnerable elderly people. It can be assumed that DomiGym reduces the frequency of falls in the long term, contributes to the preservation of mobility and independence in everyday life, including a longer stay in their own homes. References Agrawa, Y., Carey, J. P., Hoffman, H. J., Sklare, D. A., & Schubert, M. C. (2011). The modified Romberg balance test: Normative data in US adults. Otology & Neurotology, 32(8), 1309-1311. https://doi.org/10.1097/MAO.0b013e31822e5bee Beratungsstelle für Unfallverhütung BFU. (2019). Status 2019: Statistik der Nichtberufsunfälle und des Sicherheitsniveaus in der Schweiz. Strassenverkehr, Sport, Haus und Freizeit [Status 2019: Statistics on non-occupational accidents and safety levels in Switzerland. Road traffic, sports, home and leisure]. BFU. https://doi.org/10.13100/bfu.2.360.01 Marks, D. (2016). Aufstehen – Gehen – Umdrehen – Gehen – Hinsetzen – Timed-up-and-go-Test [Stand up – walk – turn around – walk – sit down – timed-up-and-go test]. physiopraxis, 14(07/08), 56-57. https://doi.org/10.1055/s-0042-108951 Mehmet, H., Yang, A. W. H., & Robinson, S. R. (2019). What is the optimal chair stand test protocol for older adults? A systematic review. Disability and Rehabilitation, 42(20), 2828-2835. https://doi.org/10.1080/09638288.2019.1575922 Meretta, B. M., Whitney, S. L., Marchetti, G. F., Sparto, P. J., & Muirhead, R. J. (2006). The five times sit to stand test: Responsiveness to change and concurrent validity in adults undergoing vestibular rehabilitation. Journal of Vestibular Research, 16(4-5). 233-243. https://doi.org/10.3233/VES-2006-164-510